STRATEGI MEMBINGKAI CITRA JEPANG DALAM TOKYO MARATHON - Syayadi, Inesha (Indonesian Association for International Relations, 2025)
This study analyzes how the Tokyo Marathon is utilized as a strategic platform to frame Japan's image. Employing a qualitative approach and interpreted through a constructivist lens, the research applies the concepts of soft power (Nye), nation branding (Anholt), and public diplomacy (Cull). Findings indicate that the Tokyo Marathon effectively projects Japan's image as a modern, efficient, and culturally rich nation. It achieves this through the appeal of cultural values (omotenashi), social inclusivity, and precise event management. The predominantly positive public reception confirms the success of these efforts in shaping international perceptions. The study concludes that the Tokyo Marathon serves as a potent instrument in non-coercively constructing Japan's global identity